The Role of the Microbiome in the Pathogenesis, Phenotype, and Treatment of Asthma - Safia Gul; Ismail Mazhar; Maryam Maqsood (Liaquat National Journal of Primary Care)
This review article examines the relationship between microbial communities and asthma, emphasizing the microbiome’s significant role in asthma development and therapy. Recent developments in the study of the microbiome have shed light on the intricate role that microbial populations play in the etiology and management of asthma. This paper examines the existing evidence regarding the involvement of microbiome dysbiosis in both the exacerbation and onset of asthma, focusing notably on its impact on inflammation and immune system regulation. The disruption of microbial balance in the gut and respiratory tract has been associated with abnormal immune responses, contributing to airway inflammation and heightened reactivity characteristic of asthma. Additionally, microbial metabolites play a substantial role in shaping airway physiology and immune regulation. Innovations in therapy, such as probiotics, prebiotics, and microbial-based treatments, aim to target the microbiome, potentially enhancing asthma management. In summary, understanding the microbiome’s role in the pathophysiology and management of asthma represents a major achievement in respiratory medicine by providing new information and prospects for customized therapy for this long-term respiratory illness.